2005
DOI: 10.1086/432499
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of X‐Ray Jets in the Microquasar H1743−322

Abstract: We report on the formation and evolution of two large-scale, synchrotron-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
245
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(279 citation statements)
references
References 28 publications
30
245
4
Order By: Relevance
“…A steady, compact, partially selfabsorbed jet (first imaged in Cyg X-1 by Stirling et al 2001) is present in this part of the "q"-shaped curve (region B in Fig. 1) and its radio luminosity L R also increases in correlation with the X-ray luminosity L X as L R ∝ L 0.71±0.1 X (Corbel et al 2000) or more accurately as L R ∝ L 0.6 X M 0.8 , where M is the mass of the black hole (Merloni et al 2003;Falcke et al 2004). The jet is mildly relativistic with a bulk Lorentz factor γ < 2 (Fender et al 2004a).…”
Section: Jets In Black-hole X-ray Binariesmentioning
confidence: 90%
“…A steady, compact, partially selfabsorbed jet (first imaged in Cyg X-1 by Stirling et al 2001) is present in this part of the "q"-shaped curve (region B in Fig. 1) and its radio luminosity L R also increases in correlation with the X-ray luminosity L X as L R ∝ L 0.71±0.1 X (Corbel et al 2000) or more accurately as L R ∝ L 0.6 X M 0.8 , where M is the mass of the black hole (Merloni et al 2003;Falcke et al 2004). The jet is mildly relativistic with a bulk Lorentz factor γ < 2 (Fender et al 2004a).…”
Section: Jets In Black-hole X-ray Binariesmentioning
confidence: 90%
“…This connection gave rise to the "fundamental plane" of black hole activity. It has been found that indeed there is a close connection between the radio and X-ray luminosity of Galactic and super massive black holes of the form L radio ∝ L 0.7 X (Corbel et al 2000(Corbel et al , 2003, linking the jet activity to the total output of the central engine. Later on, a connection of these two parameters with the black hole mass itself was found, establishing the fundamental plane of AGN and Galactic black hole activity in the form of L radio ∝ L 0.6 X M 0.8 BH (e.g.…”
Section: A Fundamental Plane Of Agn Activitymentioning
confidence: 99%
“…These have resemblance with several other typical Galactic black hole candidates (e.g., GRO J1655-40, XTE J1550-564, GX 339-4 etc.). Another important discovery of large-scale relativistic X-ray and radio jets associated with the 2003 outburst (Rupen et al, 2004;Corbel et al, 2005) put the source in the category of 'micro-quasar'. This was also reconfirmed by McClintock et al (2009), from their comparative study on the timing and the spectral properties of this source with XTE J1550-564.…”
Section: Introductionmentioning
confidence: 99%